The Southwest of the Iberian Peninsula (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
The Southwestern inscriptions from the Iberian Peninsula (frequently referred to as “Tartessian”) are a set of about 100 inscriptions dating back to the Iron Age. Probably most of them are funerary steles, which were written in a language that has not yet been identified. This paper provides a state-of-the-art of our current knowledge about these inscriptions and their language and offers prospective and insights into the possibilities of the research for further advancing in our knowledge of these inscriptions in the near future.
Keywords: Southwestern steles; Palaeohispanic languages; Palaeohispanic scripts; Iron Age; Tartessos